2015
DOI: 10.1007/s11357-015-9770-4
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Lp-PLA2 activity correlates with oxidative stress and cytokines in overweight/obese postmenopausal women not using hormone replacement therapy

Abstract: Controversy remains regarding whether there is an association between circulating lipoproteinassociated phospholipase A 2 (Lp-PLA 2 ), cytokines, and oxidative stress in healthy postmenopausal women. We investigated the influence of age on Lp-PLA 2 activity in postmenopausal women not using hormone therapy and the relationship of Lp-PLA 2 enzyme activity to serum cytokine levels and oxidative stress indices. Normal weight (n = 1284) and overweight/obese (n = 707) postmenopausal women not using hormone therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
4
5
0
Order By: Relevance
“…The circulating levels of inflammatory cytokines increase with age, leading to a subclinical inflammatory state. 8,24 Similar to previous studies, the present study showed an age-related decrease in IGF-1 level and age-related increases in IL-6 and TNF-a levels. Additionally, changes in IGF-1 expression were negatively correlated with changes in the IL-6 and TNF-a levels.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The circulating levels of inflammatory cytokines increase with age, leading to a subclinical inflammatory state. 8,24 Similar to previous studies, the present study showed an age-related decrease in IGF-1 level and age-related increases in IL-6 and TNF-a levels. Additionally, changes in IGF-1 expression were negatively correlated with changes in the IL-6 and TNF-a levels.…”
Section: Discussionsupporting
confidence: 91%
“…Low IGF‐1 levels are associated with high IL‐6 and TNF‐α levels in community‐dwelling elderly subjects . The circulating levels of inflammatory cytokines increase with age, leading to a subclinical inflammatory state . Similar to previous studies, the present study showed an age‐related decrease in IGF‐1 level and age‐related increases in IL‐6 and TNF‐α levels.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Generally, Lp‐PLA2, involved in the metabolism of LDLc, is positively associated with BMI . It is recognized that BMI is the predictor of high Lp‐PLA2 levels and CVD risk in the population . Moreover, as mentioned above, AAP, especially, olanzapine and clozapine pose a higher risk of weight gain and type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…So reducing centralized fat mass and maintaining a favorable lipid profile, antioxidant status and iron status may be important in protecting postmenopausal women from atherosclerotic disease [3].…”
Section: Introductionmentioning
confidence: 99%